â€œMemahami Retorika Laporan CSR PT Kaltim Prima Coal 2012 Melalui Analisis Framingâ€ - Arunglaâ€™biâ€™, Ranella Pasang; Kamayanti, Ari (Jurnal Ilmiah Mahasiswa FEB, 2014)
Today the company is required to no longer just for a profit-oriented, but also on the social and environmental aspects. Crash various cases of negative externalities harm people and the environment and encourage people to bring condemnation demanding the company business expectations changed to also ignore the social and environmental aspects. People's interest in a company that cares about social and environmental slowly increasing. This was disclosed by the findings PPM Institute of Management Indonesia in 2006 in Maulida (2013) that in addition to the quality and brand, a major concern of consumers in selecting products to purchase, corporate social responsibility is also an important consideration for consumers on shooping. So it was inevitable that CSR activities can boost the company's positive reputation in the eyes of stakeholders. One of the media's performance disclosure of CSR activities of the company is through the presentation of CSR report. CSR report is important because through the presence, the stakeholders knowingly reporting on all efforts made ​​by the company in realizing sustainable development, then stakehloder also may use this information in making decisions. CSR reports can also use to evaluating and improving the companies performance on social and environmental aspects. CSR report is one of the realities of products constructions. The content of CSR reports is almost entirely contained story of the company in the form of narrative. CSR report also contains positive or negative rhetoric. Rhetoric formed will produce framing. The purpose of this research is to understand the rhetoric of CSR reports of PT KPC using framing analysis and constructivism research approaches. Keywords: CSR Report, Sustainable Development, Rhetoric, Framing Analysis